B-1 cell-mediated modulation of M1 macrophage profile ameliorates microbicidal functions and disrupt the evasion mechanisms of Encephalitozoon cuniculi - Pereira, Adriano; Alvares-Saraiva, Anuska Marcelino; Konno, Fabiana Toshie de Camargo; Spadacci-Morena, Diva Denelle; Perez, Elizabeth Cristina; Mariano, Mario; Lallo, Maria Anete (PLOS Neglected Tropical Diseases, 2019)
Author summary The adaptive immune response plays a key role against Encephalitozoon cuniculi, an opportunistic fungus for T cells immunodeficient patients. The role of B cells and antibody play in natural resistance to Encephalitozoon cuniculi remains unknown. Previously, we demonstrated that B-1 deficient mice (XID), an important component of innate immunity, were more susceptible to encephalitozoonosis, despite the increase in the number of CD4+ and CD8+ T lymphocytes. Here we observed that the absence of B-1 cells was associated with a larger population of M2 macrophages, a balance between anti-inflammatory and pro-inflammatory cytokines profile, which had lower microbicidal activity against E. cuniculi infection. However, in the presence of B-1 cells, peritoneal macrophages had a M1 profile with showed increased microbicidal activity and a higher percentage of apoptotic death.